The Safety and Immunogenicity of the mRNA-BNT162b2 SARS-CoV-2 Vaccine in Hemodialysis Patients - Zitt, Emanuel; Davidovic, Tamara; Schimpf, Judith; Abbassi-Nik, Armin; Mutschlechner, Beatrix; Ulmer, Hanno; Benda, Magdalena A.; Sprenger-Mähr, Hannelore; Winder, Thomas; Lhotta, Karl (Frontiers in Immunology, 2021)
Background Hemodialysis patients are at high risk for severe COVID-19. SARS-CoV-2 vaccination related safety and immunogenicity data in these patients are rare. Methods In this observational study SARS-CoV-2-seronegative hemodialysis patients were vaccinated with two doses of the Pfizer/BioNTech mRNA-BNT162b2 vaccine (COMIRNATY® 30 µg) and followed for 90 days. Local and systemic side effects were assessed at every dialysis session during the first post-vaccination week after the first and second vaccine dose. Immunogenicity was determined four weeks after vaccination by quantifying anti-SARS-CoV-2 spike protein IgG antibodies (LIAISON® SARS-CoV-2-TrimericS IgG chemiluminescent immunoassay) expressed in binding activity units per milliliter (BAU/mL) adapted to the WHO International standard. Results Fifty patients (32% women, 68% men) with a mean (SD) age of 67.6 (14.8) years were included. Mild local reactions occurred in 38% after the first injection, and in 29.2 % with mild, in 2.1% with moderate and in 2.1% with severe degree after the second injection. Systemic reactive events occurred less often, with diarrhea (4% mild, 4% moderate) and fatigue (8% mild) being the most frequent ones. After the first injection 42% of the patients developed a positive response using the assay specific cut-off value of 33.8 binding activity units per milliliter (BAU/mL) with a median (Q1, Q3) anti-SARS-CoV-2 spike IgG concentration of 20.0 (11.7, 51.0) BAU/mL. After the second injection the percentage of seropositive patients increased to 97.9% with an anti-SARS-CoV-2 spike IgG concentration of 1075 (290.8, 1735) BAU/mL. Higher age and immunosuppression were associated with lower, calcitriol treatment and prior seroconversion to hepatitis B vaccination with significantly higher antibody concentration. Conclusions The mRNA-BNT162b2 SARS-CoV-2 vaccine appears to be safe and well-tolerated and shows a high immunogenicity in hemodialysis patients.